# Perform the operations indicated.B) (5x^2y-6xy^2+2)+(-8x^2y+12xy^2-6)  C)(3x^4-4x^2-18)-(2x^4+3x^3+6)

justaguide | College Teacher | (Level 2) Distinguished Educator

Posted on

The results when the given operations are performed on the expressions are:

(5x^2y-6xy^2+2)+(-8x^2y+12xy^2-6)

= 5x^2y - 6xy^2 + 2 - 8x^2y + 12xy^2 - 6

= 5x^2y - 8x^2y - 6xy^2 + 12xy^2 + 2 - 6

= -3x^2y + 6xy^2 - 4

(3x^4-4x^2-18)-(2x^4+3x^3+6)

= 3x^4 - 4x^2 - 18 - 2x^4 - 3x^3 - 6

= 3x^4 - 2x^4 - 4x^2 - 3x^3 - 18 - 6

= x^4 - 3x^3 - 4x^2 - 24

The required results are: (5x^2y-6xy^2+2)+(-8x^2y+12xy^2-6)  = -3x^2y + 6xy^2 - 4 and (3x^4-4x^2-18)-(2x^4+3x^3+6) = x^4 - 3x^3 - 4x^2 - 24

oldnick | (Level 1) Valedictorian

Posted on

WRONG C)!

`C)(3x^4-4x^2-18)-(2x^4+3x^3+6)=`

`=3x^4-4x^2-18-2x^4-3x^3-6=`

`=3x^4-2x^4-3x^3-4x^2-18-6=`

`=x^4-3x^3-4x^2-24`

oldnick | (Level 1) Valedictorian

Posted on

`B) (5x^2y-6xy^2+2)+(-8x^2y+12xy^2-6)=`

`=5x^2y-8x^2y -6xy^2+12xy^2+2-6=```

`=-3x^2y-6xy^2-4`

`C) (3x^4-4x^2-18)-(2x^4+3x^3+6)=`

`=3x^4-4x^2-18-2x^4-3x^3-6=`

`=3x^4-2x^4 -4x^2-3x^2-18-6=`

`=2x^4-7x^2-24`